Striking first : preemptive and preventive attack in U.S. national security policy - Mueller, Karl P. (Rand Corporation monograph series., 2006)
Following the terrorist attacks against the United States on September 11, 2001, U.S. leaders recast the national security strategy to place greater emphasis on the threats posed by terrorists and by states from which they might acquire weapons of mass destruction, and announced that in the future the United States would take advantage of opportunities to strike at potential adversaries before they attacked. RAND Project Air Force examined the nature and implications of this doctrine of striking first. This study focused on three central questions: First, under what conditions is preemptive or preventive attack worth considering or pursuing as a response to perceived security threats? Second, what role should such strategies be expected to play in future U.S. national security policy? Finally, what implications do these conclusions have for planners and policymakers in the U.S. Air Force and the other armed services as they design military capabilities and strategies to deal with national security threats in the next decade? The study concluded preparing for such operations should not be a key driver for change in U.S. military capabilities because large-scale U.S. first strike will be infrequent and present few unique operational military requirements, although the intelligence requirements for these strategies are highly demanding. Planners should also recognize that this doctrine may affect the types of threats posed against U.S. forces and interests by potential adversaries.